Spatial Variability of Sliding Plane on Volcanic Region. Case Study of Sta 21+200 Cisumdawu Toll Road - Arsyad, Ahmad Kemal; Wijaya, Martin; Johan, Albert; Pramono Rahardjo, Paulus (Indonesian Geotechnical Journal, 2024)
Landslide can be caused either by natural phenomenon or due to human intervention. Regardless of the triggering factor, once landslide occurs, sliding plane in the form of discontinuity or sometimes referred as sliding plane is formed. Identifying the location and geometry of the sliding plane is important in determining the location of the reinforcement to rehabilitate slope failure. However, it is often difficult to locate the location and geometry of the sliding plane as the sliding direction is also difficult to ascertain. In this paper, slope failure which occurred in STA 21+200 of Cisumdawu toll road is used as case study. Variability of the sliding planes are investigated based on the location of the concrete overbreak that occurred during the bored pile construction on Tuff (volcanic soils) in Sumedang Region. Sliding planes are also estimated based on the soil investigation and pile boring records. The proposed solution is to reinforce the bored piles that did not penetrate into the hard layer with ground anchors installed at the pile cap.